2017
DOI: 10.1039/c6cp07755b
|View full text |Cite
|
Sign up to set email alerts
|

Slip divergence of water flow in graphene nanochannels: the role of chirality

Abstract: Graphene has attracted considerable attention due to its characteristics as a 2D material and its fascinating properties, providing a potential building block for nanofabrication. In nanochannels the solid-liquid interface plays a non-negligible role in determining the fluid dynamics. Therefore, for an optimal design of nanofluidic devices, a comprehensive understanding of the slippage in a water flow confined between graphene walls is important. In nanoconfinement, experimental and computational studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 71 publications
4
58
0
Order By: Relevance
“…The reported data about slip length are widely scattered, from less than a nanometer to several micrometers. [96] For the cases of water in CNTs, the numerical simulation gives 0.81-5.42 nm of slippage [98] while experimental values are 8-53 nm, [99] depending on the channel size. Slip lengths at the scale of micrometer are not unusual, especially in experimental works.…”
Section: Flow Enhancement and Surface Slipmentioning
confidence: 94%
See 1 more Smart Citation
“…The reported data about slip length are widely scattered, from less than a nanometer to several micrometers. [96] For the cases of water in CNTs, the numerical simulation gives 0.81-5.42 nm of slippage [98] while experimental values are 8-53 nm, [99] depending on the channel size. Slip lengths at the scale of micrometer are not unusual, especially in experimental works.…”
Section: Flow Enhancement and Surface Slipmentioning
confidence: 94%
“…However, the slip lengths at the scale of nanometer are dominant in both numerical and experimental works. On graphene surface, the slip length for water is around 30-100 nm in molecular dynamics simulations [90,91,96] and 8 nm in experiments, [97] where the shear stress or even the chirality may make a difference. [96] For the cases of water in CNTs, the numerical simulation gives 0.81-5.42 nm of slippage [98] while experimental values are 8-53 nm, [99] depending on the channel size.…”
Section: Flow Enhancement and Surface Slipmentioning
confidence: 99%
“…To elucidate the effect of externally applied electric fields in capillary filling of water in hydrophilic silica nanopores, we conduct a series of all-atom MD simulations using FAST-TUBE, a molecular dynamics simulation package which has widely been used to investigate fundamental fluid dynamics under nanoconfinement. 29,42,45,[63][64][65] Water molecules are described using the simple point charge SPC/E model 66 and the silica atoms by the TTAMm model developed by Guissani and Guillot 67 which is a modification of the original TTAM model. 68 Water-silica interactions are described using Coulomb and Buckingham potentials calibrated in our previous study 69 wherein the experimental value of the water contact angle reported by Thamdrup et al 70 in studies of capillary filling is used as criterion to calibrate the potential parameters.…”
Section: Methodsmentioning
confidence: 99%
“…68 Water-silica interactions are described using Coulomb and Buckingham potentials calibrated in our previous study 69 wherein the experimental value of the water contact angle reported by Thamdrup et al 70 in studies of capillary filling is used as criterion to calibrate the potential parameters. For further details of the potentials used here, we refer readers to Zambrano et al 69 We have chosen the SPC/E water model not only to be consistent with our previous works, 42,45,63,69 but also due to its simplicity and quantitative agreement with experiments to yield water reorientation and hydrogen bond dynamics. 44,51,[71][72][73] Moreover, studies have found that the value of the surface tension for the SPC/E model is in good agreement with experimental results.…”
Section: Methodsmentioning
confidence: 99%
“…For confined geometries the hydrodynamic equations are no longer valid, and in this case, the use of the no-slip boundary condition is at least questionable. Many experimental [1][2][3][4][5][6][7][8], theoretical, and computational [9][10][11][12][13][14][15] results report that there are several flow boundary conditions consistent with the fluid behavior and mobility [16][17][18][19] beyond the no-slip boundary condition. The amount of slip is usually measured through the magnitude of the slip length, defined as the ratio between the shear rate and the slip velocity [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%